2015
DOI: 10.1136/injuryprev-2015-041599
|View full text |Cite
|
Sign up to set email alerts
|

Masculine discrepancy stress, substance use, assault and injury in a survey of US men

Abstract: To understand and ultimately prevent injury and behavioural health outcomes associated with masculinity, we assessed the influence of masculine discrepancy stress (stress that occurs when men perceive themselves as falling short of the traditional gender norms) on the propensity to engage in stereotypically masculine behaviours (eg, substance use, risk taking and violence) as a means of demonstrating masculinity. Six-hundred men from the USA were recruited via Amazon’s Mechanical Turk (MTurk) online data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 15 publications
3
37
0
Order By: Relevance
“…These scripts indicate that women have "few sexual needs" and "view sex as synonymous with love," whereas men have "strong sexual needs" and "are obsessed with sex." Male perpetrators of IPV have a strong adherence to sexual cultural scripts (Willie, Khondkaryan, Callands, & Kershaw, 2018c) and traditional masculine norms (Reidy, Berke, Gentile, & Zeichner, 2015;Santana, Raj, Decker, La Marche, & Silverman, 2006), which could make them believe that their sexual infidelity is legitimate. For women experiencing IPV, accusations of sexual infidelity could be a trigger for a violent event (Buss & Duntley, 2014;Nemeth, Bonomi, Lee, & Ludwin, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These scripts indicate that women have "few sexual needs" and "view sex as synonymous with love," whereas men have "strong sexual needs" and "are obsessed with sex." Male perpetrators of IPV have a strong adherence to sexual cultural scripts (Willie, Khondkaryan, Callands, & Kershaw, 2018c) and traditional masculine norms (Reidy, Berke, Gentile, & Zeichner, 2015;Santana, Raj, Decker, La Marche, & Silverman, 2006), which could make them believe that their sexual infidelity is legitimate. For women experiencing IPV, accusations of sexual infidelity could be a trigger for a violent event (Buss & Duntley, 2014;Nemeth, Bonomi, Lee, & Ludwin, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of a variety of groups, rather than investigating one speci c cohort of gang members, allows for differences to be evaluated. As neither studies identi ed a difference between the ethnicity of groups divided by level of gang involvement, this suggests no association with gang violence (24,33) .…”
Section: Demographymentioning
confidence: 82%
“…All four studies investigating age found a positive association between knife crime and adolescence (21,26,30,32) . compared to other age groups, is positively associated with being in a gang (23,26,33) . Densley et al (WOE=M) interviewed 69 self-described gang members, recruited from six London boroughs experiencing high levels of socioeconomic deprivation, with an age range of 13-34 (mean age 20).…”
Section: Demographymentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, in a sample of adolescent boys, discrepancy stress positively predicted a perpetration of sexual violence (Reidy, Smith‐Darden, Cortina, Kernsmith, & Kernsmith, ). Outside the confines of romantic relationships, finally, participants higher in discrepancy stress had a higher lifetime frequency of engagement in assaults with a weapon and assaults causing injury (Reidy, Berke, Gentile, & Zeichner, ). These results meaningfully buttress the validity of masculine discrepancy stress as a construct that conforms to the assumptions of the Gender Role Strain Paradigm (Pleck, ), finding perceptions of falling short of male gender role norms to be both stressful and predictive of violence.…”
Section: Masculine Discrepancy Stress: a Closer Lookmentioning
confidence: 99%